Pengaruh Audit Manajemen Sumber Daya Manusia terhadap Kinerja Karyawan di Rumah Sakit Umum Daerah Kota Bekasi - Ilham Rachdiansyah; Joni Tesmanto (LPPM IAI Nasional Laa Roiba Bogor, 2021)
This study aims to analyze the effect of Human Resources Management Audit on Employee Performance in General Hospital Bekasi. This study is a causal-comparative research. This study population is the entire General Hospital Bekasi employees totaling 158 respondents. The selection of the sample using Cluster Random Sampling method. The number of samples was 80 respondents, derived from four divisions: medical division (8 respondents), paramedic (32 respondents), medical support (10 respondents), and general (30 respondents). The data used are primary data in the form of a questionnaire. Prior to the study, first conducted trials-test with the instrument validity-test and reliability-test involving 20 employees of a General Hospital Bekasi were not involved back at the time of the study. Analysis prerequisite- test including normality-test, linearity-test, multicolinearity-test, and heteroscedasticity-test. The hypothesis-test in this study using simple-regression analysis. The results of this study indicate the Human Resources Management Audit have a significant and positive influence on Employee Performance in General Hospital Bekasi indicated by r2 value of 0.518, the significant value smaller than level of significant (0.000 < 0.050) and the regression line equation is Y = 0.813 + 0.766X. Keywords : Management Audit, Human Resources, Employee Performance.